The Implementation of Work Discipline in Improving Employee Performance At Hilimegai South Nias Regency - Ndruru, Yance Erni Kasih; Mendrofa, Cardinal Pranatal; Lase, Delipiter; Laia, Otanius (Journal of International Multidisciplinary Research, 2024)
The focus of research in this study is to understand the symptoms of objects thoroughly so that researchers can identify existing problems and formulate problems to be studied. This research focused on the application of work discipline to improve employee performance at the Hilimegai Sub-district Office, South Nias Regency with a descriptive approach. The purpose of descriptive research is to describe and analyze research data related to phenomena, social activities, and human attitudes in various situations. At the Hilimegai Sub-district Office of South Nias Regency, the implementation of work discipline is quite good because most employees arrive on time although a small number are sometimes late due to long distances from home, but this is not used as an excuse and they still obey the rules. Employees there also always take care of office equipment as a form of discipline. They also show high responsibility by diligently completing work and are willing to work overtime to achieve work targets. However, adherence to the rules still needs to be improved because some employees often neglect their duties. Employees at the Hilimegai Subdistrict Office of South Nias Regency work for 8 hours a day, from 8 am to 4 pm, and always follow the rules that apply in their office.